Efforts to Prevent Obesity in Primary School Children Through Intervention Nutritional Education and Physical Activity – School Based - Rina Oktaria; Meri Neherta; Deswita Deswita (LPPM STIKES KENDAL, 2020)
One of the problems of excess nutrition that occurs in children and gets special attention in the world of health is obesity. The purpose of this study was to analyze the effectiveness of school-based nutrition education interventions and school-based physical activity in an effort to prevent obesity in school-age children. This research method starts from searching data using five databases, namely Science Direct, Taylor & Francis Online ( Tandfonline ), PubMed, DOAJ and SAGE with a range of 2015-2020 with a total of 2,125 articles. Articles searched for with the keyword